2007
DOI: 10.3892/or.17.6.1333
|View full text |Cite
|
Sign up to set email alerts
|

Increased synthesis of indoleamine-2,3-dioxygenase protein is positively associated with impaired survival in patients with serous-type, but not with other types of, ovarian cancer

Abstract: We previously reported that indoleamine-2,3dioxygenase (IDO) is associated with paclitaxel resistance and that IDO serves as a marker of poor prognosis in ovarian serous adenocarcinomas (SA). In this study, to explore the role of IDO in the development of various histological types of ovarian cancer, we further examined IDO expression not only in SA but also in other types of ovarian cancers. Expression of IDO protein was analyzed by immunohistochemistry for a total of 122 ovarian cancers including 40 SA, 67 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 19 publications
3
59
0
2
Order By: Relevance
“…However, 21 out of 60 TDLNs analyzed had a high density of IDO þ cells, and these have been associated with a decreased 5-year survival rate (33). Finally, it has been observed that patients with ovarian carcinoma presenting high IDO expression, as evaluated by IHC (15) or global gene expression profiles (34,35), have a shorter postsurgery life expectancy. Only 2 studies have reported results contradictory to those discussed above.…”
Section: Association With Patient Survivalmentioning
confidence: 99%
“…However, 21 out of 60 TDLNs analyzed had a high density of IDO þ cells, and these have been associated with a decreased 5-year survival rate (33). Finally, it has been observed that patients with ovarian carcinoma presenting high IDO expression, as evaluated by IHC (15) or global gene expression profiles (34,35), have a shorter postsurgery life expectancy. Only 2 studies have reported results contradictory to those discussed above.…”
Section: Association With Patient Survivalmentioning
confidence: 99%
“…In cancer, local tryptophan depletion, kynurenine, and other KP metabolites foster an immunosuppressive tumor microenvironment (5,6). Recent studies have identified IDO1 in both hematologic cancers and solid tumors (e.g., breast cancer, lung cancer, glioblastoma) (7) with increased IDO1 expression linked to poorer outcomes (8)(9)(10). In addition to IDO1, TDO2 may also play a prominent role in glioma pathophysiology (11,12).…”
mentioning
confidence: 99%
“…Wyraźną korelację między ekspresją IDO a krótszym czasem przeżycia u chorych z zaawansowanym surowiczym rakiem jajnika (nie z innymi typami histologicznymi) potwierdziły badania Takao i wsp. [16]. Inaba i wsp.…”
Section: Dyskusjaunclassified